ANALISIS MODEL MATEMATIKA PENYEBARAN PENYAKIT ISPA - Nurfadilah; Hikmah; Fardinah (Program Studi Matematika Universitas Sulawesi Barat, 2021)
Acute Respiratory Infection (ARI) is an infectious disease caused by bacteria and an unhealthy environment. The number of sufferers of this disease tends to increase and expand. The purpose of this study was to construct a mathematical model of the SEHAR epidemic (Suspectible-Exposed-Infected-Asthma-Recovered), analyze the stability of the equilibrium point and simulate the model. The results obtained are the SEHAR mathematical model for the spread of ARI disease which produces a disease-free equilibrium point and an endemic equilibrium point from the model. The method used is the stability analysis of the model using the Routh-Hurwitz Criteria to identify the characteristics of the eigenvalues. From the results of the stability analysis, it is found that the disease-free equilibrium point Eo and the endemic equilibrium point E1 are stable if the conditions for the relationship between parameters are met. At the end of the study, a simulation model was given using the Maple application